10-minute make-up 50 step-by-step looks from fresh and natural to catwalk chic - Entrup, Boris 1978- (Dorling Kindersley Limited, 2014)
Offers step-by-step, illustrated instructions for fifty versatile looks that can be created in only ten minutes, including detailed information on basic techniques, products, equipment, and special makeup tips and tricks. --Publisher's description.